Anatomic and Embryological Aspects of the Cardiovascular System of Albino Wistar Rats - De Russi, Brenno Marco; Carvalho, Camila Albuquerque Melo (Journal of Morphological Sciences, 2019)
The Wistar albino rat is the animal most commonly used in scientific research around the world. Knowledge of the anatomy of the body of these animals is key in the research field, especially in cases when the research requires experimental surgery. Descriptive literature on the morphology of the cardiovascular system of these animals, particularly the heart, is old and difficult to access. Publications in journals are not readily available, and books approach the subject in a superficial way. The aim of this study is to research, organize, and translate the literature on the anatomy and embryology of the cardiovascular system of the albino Wistar rat to facilitate the use of this information in future research that requires the knowledge of the anatomy of these animals, for example, experimental surgery research.
Keywords: anatomy; embryology; heart; morphology; rat